Preparation method and application of composite material NiSeZn (g-C3N4) / CNFs
By modifying carbon nanofibers and growing NiSeZn (g-C3N4) and combining with high-temperature and high-pressure calcining process, nanocomposite NiSeZn (g-C3N4)/CNFs with excellent performance were prepared, which solved the insufficient performance of composite bipolar plates and The issue of environmental pollution.
Patent Information
- Application Number
- CN202411406374.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The existing composite bipolar plates have shortcomings in terms of mechanical, electrical conductivity, thermal conductivity and corrosion resistance, especially the poor dispersion effect of carbon-based materials and environmental pollution problems.
Using the preparation method of nanocomposite NiSeZn(g-C3N4)/CNFs, carbon nanofibers were subjected to alkali treatment, graft modification and freeze-denatation treatment, and NiSeZn(g-C3N4) was grown on it, followed by a second High temperature and high pressure calcination process enhances the performance of the material.
The electrical conductivity, thermal conductivity, flexural strength and compressive strength of the composite material are significantly improved, and the raw materials used are safe, the cleaning liquid can be recycled, reducing waste liquid and environmental pollution.
Smart Images

Figure HDA0005076698800000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nano-composite bipolar plate materials, and specifically relates to a preparation method and application of a composite material NiSeZn(g-C3N4) / CNFs. Background Art
[0002] Bipolar plates are an important component of hydrogen fuel cells, with functions such as connecting single modules, separating reaction gases, collecting current, dissipating heat and draining water.
[0003] Bipolar plates can be divided into metal bipolar plates and composite bipolar plates according to their materials. Metal bipolar plates (such as patent publication number CN109560305A) have good mechanical, electrical and thermal conductivity, but poor corrosion resistance, so a coating is generally added to the surface (such as patent publication number CN210628419U), and the mechanical, electrical and thermal conductivity of the coating will also affect the performance of the bipolar plate. Composite bipolar plates can have excellent mechanical, electrical, thermal and corrosion resistance properties.
[0004] At present, there are many studies on composite bipolar plates, such as patent publication number CN117747169A, which includes a resin matrix, a curing agent and a modified conductive filler, and the modified conductive filler is a carbon-based material treated with a modifier; the modifier includes any one of styrylpyrene butyrate, polybutylphenylacetate, polyacrylic acid, polystyrene butyl acrylate or polystyrene, or a combination of at least two. It is obtained by mixing a resin matrix, a curing agent, and a modified conductive filler to obtain a coating slurry, which is then coated on the surface of a carbon fiber prepreg, and a composite bipolar plate is obtained after a pressing treatment. However, due to the shortcomings of poor dispersion and easy entanglement and agglomeration of carbon-based materials, the modified effect of the mixed coating slurry is unstable, and the internal morphology of the carbon fiber is not changed by surface coating treatment of the carbon fiber, and the reinforcement effect is not good.
[0005] Another example is patent publication number CN117352765A, which soaks an expanded graphite prefabricated plate in a solution containing aniline, with the molar mass ratio of aniline to expanded graphite prefabricated plate being (0.3-0.8) mol:10g, and performs in-situ polymerization, and obtains an EG-PANI composite material after post-treatment; the EG-PANI composite material is compounded with a phenolic resin by a vacuum impregnation method to obtain a PANI-EG-PF composite material; the PANI-EG-PF composite material is subjected to a hot pressing molding process to obtain a hydrogen fuel cell composite bipolar plate. However, the amount of aniline used is large and the toxicity is high. The immersion method will leave a large amount of impregnation waste liquid, which will cause immeasurable harm to the environment. Moreover, the comprehensive performance of the composite material also needs to be further improved. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a nanocomposite material NiSeZn(g-C3N4) / CNFs and a preparation method thereof. To achieve the above objectives, the present invention adopts the following technical solutions:
[0007] A method for preparing a composite material NiSeZn(g-C3N4) / CNFs comprises the following steps:
[0008] S1, adding ethylene glycol to the carbon nanofibers after alkali treatment, adding silane coupling agent and melamine to carry out graft modification after ultrasonic treatment, washing the modified carbon nanofibers with water, and recovering the washing liquid;
[0009] S2, adding the cleaning solution to dopamine and CE resin, stirring and reacting, drying, roasting, cooling, and then grinding the roasted product to nanometer scale;
[0010] S3, preparing an aqueous solution containing melamine and ZnSO4 as a dispersion system A;
[0011] S4, dispersing the modified carbon nanofibers obtained in step S1 in ethanol, adding nano-sized nickel selenide and the calcined product obtained in S2, and heating to obtain a dispersion system B;
[0012] S5, adding dispersion system B to dispersion system A, and centrifuging after ultrasonic treatment;
[0013] S6. Calcine the centrifuged sample to obtain the composite material NiSeZn(g-C3N4) / CNFs.
[0014] For the composite material as described above, preferably, in step S1, the alkali treatment is soaking in an alkaline solution; the soaking time is 1 to 2 hours, the amount of ethylene glycol used is 1:1 to 3 in a volume mass ratio of ethylene glycol to carbon nanofibers, and the unit is L:kg; the ultrasonic time is 20 to 30 minutes.
[0015] Furthermore, the alkaline solution is a sodium hydroxide solution with a concentration of 20-40wt%; and the soaking time is 1-2h.
[0016] For the composite material as described above, preferably, in step S1, the mass ratio of carbon nanofiber, silane coupling agent and melamine is 50-85:1.7-3.6:0.8-1.5. Further, the silane coupling agent is N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane coupling agent.
[0017] For the composite material as described above, preferably, in step S1, the cleaned modified carbon nanofibers need to be frozen denatured at a temperature of -10 to 0°C for 3 to 10 hours. Furthermore, the frozen denaturation temperature is -5 to 0°C for 5 to 8 hours.
[0018] The composite material as described above, preferably, in step S2, the mass ratio of the cleaning liquid to dopamine is 100-125:6.8-9.3, and the mass ratio of dopamine to CE resin is 1-2:3-7;
[0019] The stirring reaction temperature is 50-65°C, and the reaction time is 24-40h; the calcination temperature is 200-320°C, and the calcination time is 50-70min; and the powder is ground to 200-600nm.
[0020] For the composite material as described above, preferably, in step S3, the mass ratio of melamine to ZnSO4 is 15-21:7.35-9, wherein the mass concentration of melamine is 13%-20%.
[0021] For the composite material as described above, preferably, in step S4, nickel selenide is added at a mass ratio of nickel selenide to carbon nanofiber of 0.1-0.3:1; the heating temperature is 80° C., and the heating time is 15-20 min.
[0022] For the composite material as described above, preferably, in step S5, the adding speed of dispersion system B into dispersion system A is less than 1 L / min, and the ultrasonic treatment time is 1.5 to 2.3 h.
[0023] For the composite material as described above, preferably, in step S6, the calcination is divided into two calcinations, the first calcination process is calcination at 600-750°C for 2.1-2.3h; the second high temperature and high pressure calcination process is calcination at 10-11Gpa and 1100-1200°C for 5-10min.
[0024] The composite material NiSeZn(g-C3N4) / CNFs obtained by the preparation method as described above is used in the preparation of hydrogen fuel cell composite bipolar plates.
[0025] The beneficial effects of the present invention are:
[0026] The present invention provides a method for preparing a nanocomposite material NiSeZn(g-C3N4) / CNFs, wherein the carbon nanofibers are firstly subjected to an alkali treatment, and then the carbon nanofibers are grafted and modified by an N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane coupling agent (Z-6020), and then subjected to a freezing denaturation treatment; thereafter, NiSeZn(g-C3N4) is grown on the modified carbon nanofibers to prepare NiSeZn(g-C3N4) / CNFs, and then subjected to a secondary high-temperature and high-pressure calcination process, thereby enhancing the electrical conductivity, thermal conductivity, flexural strength and compressive strength of the composite material. The preparation method provided by the present invention uses safe raw materials, and the cleaning liquid can be recycled, which can reduce the amount of waste liquid generated and avoid the environmental damage caused by the immersion method.
[0027] The nanocomposite material NiSeZn(g-C3N4) / CNFs of the present invention has high electrical conductivity (195S / cm), high thermal conductivity (6.3×10 w / mk), good flexural strength (51.7 MPa) and compressive strength (91.4 MPa), and excellent comprehensive performance, which is conducive to the application in hydrogen fuel cell composite bipolar plates. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The present invention is a flow chart of a method for preparing a nanocomposite material NiSeZn(g-C3N4) / CNFs. DETAILED DESCRIPTION
[0029] The inventive principle of the present invention is a nanocomposite material NiSeZn(g-C3N4) / CNFs and a preparation method thereof, which includes: 1. preparing modified carbon nanofibers (CNFs); alkali treatment; grafting modification; and freeze denaturation treatment; 2. growing NiSeZn(g-C3N4) on the modified carbon nanofibers to prepare NiSeZn(g-C3N4) / CNFs. Specifically, the carbon nanofibers are firstly treated with alkali, and then the carbon nanofibers are grafted and modified by N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane coupling agent, and then subjected to freeze denaturation treatment; then NiSeZn(g-C3N4) is grown on the modified carbon nanofibers to prepare NiSeZn(g-C3N4) / CNFs, and then subjected to a secondary high temperature and high pressure calcination process, thereby enhancing the electrical conductivity, thermal conductivity, flexural strength and compressive strength of the composite material. Both nickel selenide (NiSe) and zinc (Zn) have high discharge specific capacity. The composite of the two can improve the discharge specific capacity of the electrode material; the composite with graphite phase carbon nitride (g-C3N4) can further improve the electronic conductivity; and the strength of the composite material can be improved by modifying it onto carbon nanofibers.
[0030] The following examples are used to further illustrate the present invention, but should not be construed as limiting the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the present invention all belong to the scope of the present invention.
[0031] Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, all reagents used in the present method are of analytical grade or above.
[0032] Example 1
[0033] A method for preparing a composite material NiSeZn(g-C3N4) / CNFs, the schematic diagram of which is shown in FIG. Figure 1 As shown, the specific steps include:
[0034] 1. Preparation of modified carbon nanofibers (CNFs)
[0035] Alkali treatment: 50 g of carbon nanofibers were treated with 32 wt % sodium hydroxide solution for 1.5 h;
[0036] Graft modification: the alkali-treated carbon nanofibers were then placed in 50 mL of ethylene glycol, subjected to ultrasonic dispersion treatment for 20 min, and then 3.6 g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane coupling agent (Z-6020) and 0.8 g of melamine were added, heated to 80°C, and ultrasonic dispersion treatment was continued for 1 h; the grafted modified carbon nanofibers were obtained, which were spray-washed with water and then centrifuged to recover the washing liquid;
[0037] Freeze denaturation treatment: The grafted modified carbon nanofibers were placed in a -5°C freezer for 8 h, then freeze-dried in a vacuum drying oven, and ground and sieved to 200 mesh;
[0038] Second, grow NiSeZn(g-C3N4) on grafted modified carbon nanofibers to prepare NiSeZn(g-C3N4) / CNFs;
[0039] Drying and calcining of the cleaning solution: add 9.3 g dopamine and 19.6 g CE resin to 100 g of the cleaning solution, stir and react at 50°C for 40 h, dry and then calcine at 200°C for 70 min, and grind to nanometer level (200 nm) after cooling;
[0040] In the present invention, the cleaning liquid can be recycled, which can reduce the amount of waste liquid;
[0041] Preparation of dispersion system A: 15 g of melamine was dissolved in 80 g of deionized water, 13 g of ZnSO4·7H2O was added, and the mixture was heated in a water bath at 80°C with stirring for 40 min to obtain dispersion system A;
[0042] Preparation of dispersion system B: Disperse the CNFs obtained above in an ethanol solution, add 8.5 g of nano-sized nickel selenide and the above calcined product, and heat in a water bath at 80° C. with stirring for 20 min to obtain dispersion system B;
[0043] Blending loading: Add dispersion system B into dispersion system A at a rate of less than 1 L / min; ultrasonic dispersion treatment for 1.5 h, followed by centrifugation;
[0044] First calcination process: the sample was calcined at 600 °C for 2.3 h. The obtained sample was named NiSeZn(g-C3N4) / CNFs. After that, the sample was ground and sieved with 500 mesh.
[0045] 3. Secondary high temperature and high pressure calcination process: Place the NiSeZn(g-C3N4) / CNFs sample in a top press and calcine at 10 GPa and 1200°C for 5 min.
[0046] Example 2
[0047] 1. Preparation of modified carbon nanofibers (CNFs)
[0048] Alkali treatment: 85 g of carbon nanofibers were treated with 25 wt % sodium hydroxide solution for 1-2 h;
[0049] Graft modification: the alkali-treated carbon nanofibers were then placed in 50 mL of ethylene glycol, subjected to ultrasonic dispersion treatment for 30 min, and then 1.7 g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane coupling agent (Z-6020) and 1.5 g of melamine were added, heated to 55° C., and ultrasonic dispersion treatment was continued for 3 h to obtain graft-modified carbon nanofibers; the graft-modified carbon nanofibers were spray-washed with water and then centrifuged to recover the washing liquid;
[0050] Freeze denaturation treatment: The grafted modified carbon nanofibers were placed in a freezer at 0°C for 5 h, and then freeze-dried in a vacuum drying oven, and ground and sieved to 300 mesh;
[0051] Second, grow NiSeZn(g-C3N4) on grafted modified carbon nanofibers to prepare NiSeZn(g-C3N4) / CNFs;
[0052] Drying and calcining of the cleaning solution: add 6.8 g dopamine and 31.2 g CE resin to 125 g cleaning solution, stir and react at 65°C for 24 h, dry and then calcine at 320°C for 50 min, and grind to nanometer level (600 nm) after cooling;
[0053] Preparation of dispersion system A: 21 g of melamine was dissolved in 75 g of deionized water, 15.8 g of ZnSO4·7H2O was added, and the mixture was heated in a water bath with stirring for 25 min to obtain dispersion system A;
[0054] Preparation of dispersion system B: Disperse the CNFs obtained above in an ethanol solution, add 15 g of nano-sized nickel selenide and the above calcined product, and heat in a water bath at 80° C. with stirring for 15 min to obtain dispersion system B;
[0055] Blending loading: Add dispersion system B into dispersion system A at a rate of less than 1 L / min; ultrasonic dispersion treatment for 2.3 h, followed by centrifugation;
[0056] First calcination process: the sample was calcined at 750 °C for 2.1 h. The obtained sample was named NiSeZn(g-C3N4) / CNFs. After that, the sample was ground and sieved with 600 mesh.
[0057] 3. Secondary high temperature and high pressure calcination process: Place the NiSeZn(g-C3N4) / CNFs sample in a top press and calcine at 11 GPa and 1100°C for 10 min.
[0058] Example 3
[0059] 1. Preparation of modified carbon nanofibers (CNFs)
[0060] Alkali treatment: 68 g of carbon nanofibers were treated with 28 wt % sodium hydroxide solution for 2 h;
[0061] Graft modification: the alkali-treated carbon nanofibers were then placed in 50 mL of ethylene glycol, subjected to ultrasonic dispersion treatment for 25 min, 2.9 g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane coupling agent (Z-6020) and 1.2 g of melamine were added, heated to 72° C., and ultrasonic dispersion treatment was continued for 1.6 h; graft-modified carbon nanofibers were obtained, the graft-modified carbon nanofibers were spray-washed with water, and then centrifuged to recover the washing liquid;
[0062] Freeze denaturation treatment: The grafted modified carbon nanofibers were placed in a -3°C freezer for 6 h, then freeze-dried in a vacuum drying oven, and ground and sieved through 260 mesh;
[0063] Second, growing NiSeZn(g-C3N4) on modified carbon nanofibers to prepare NiSeZn(g-C3N4) / CNFs;
[0064] Drying and calcining of the cleaning solution: add 8.3 g dopamine and 20.9 g CE resin to 105 g cleaning solution, stir and react at 55 °C for 30 h, dry and then calcine at 240 °C for 60 min, and grind to nanometer level (400 nm) after cooling;
[0065] Preparation of dispersion system A: 18 g of melamine was dissolved in 77 g of deionized water, 14.2 g of ZnSO4·7H2O was added, and the mixture was heated in a water bath at 80°C with stirring for 28 min to obtain dispersion system A;
[0066] Preparation of dispersion system B: Disperse the CNFs prepared above in an ethanol solution, add 10.5 g of nano-sized nickel selenide and the above calcined product, and heat in a water bath at 80° C. with stirring for 18 min to obtain dispersion system B;
[0067] Blending loading: Add dispersion system B into dispersion system A at a rate of less than 1 L / min; ultrasonic dispersion treatment for 2 h, followed by centrifugation;
[0068] First calcination process: the sample was calcined at 680 °C for 2.2 h. The obtained sample was named NiSeZn(g-C3N4) / CNFs. After that, the sample was ground and sieved with 550 mesh.
[0069] 3. Secondary high temperature and high pressure calcination process: Place the NiSeZn(g-C3N4) / CNFs sample in a top press and calcine at 10.6 GPa and 1180°C for 7 min.
[0070] Comparative Example 1
[0071] The difference from Example 1 is that the mass ratio of carbon nanofiber, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane coupling agent (Z-6020) and melamine is 100:1:0.5.
[0072] Comparative Example 2
[0073] The difference from the first embodiment is that the mass ratio of nano-scale nickel selenide to carbon nanofiber is 0.5:1.
[0074] Comparative Example 3
[0075] The difference from Example 1 is that: the second high temperature and high pressure calcination process: the sample is placed in a top press and sintered at 15 Gpa and 1500° C. for 15 minutes.
[0076] Comparative Example 4
[0077] The difference from Example 1 is that after the cleaning liquid is dried and roasted, it is cooled and ground to 200 mesh.
[0078] Test experiment
[0079] The following tests were performed on the composite bipolar plates prepared from the nanocomposite materials of Examples 1, 2, 3 and Comparative Examples 1, 2, 3 and 4: electrical conductivity (S / cm), thermal conductivity (×10 w / mk), flexural strength (MPa), and compressive strength (MPa). The test standards were in accordance with GB / T20042.6-2011 "Proton Exchange Membrane Fuel Cell Part 6: Bipolar Plate Characteristics Test Method". The results are shown in Table 1 below.
[0080] Table 1 Performance of each embodiment and comparative example material
[0081] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Conductivity 192 186 195 180 191 167 155 Thermal conductivity 5.9 5.4 6.3 4.3 5.1 4.8 4.6 Bending strength 49.8 43.9 51.7 43.9 36.8 30.7 40.9 Compressive strength 80.7 88.2 91.4 84.4 81.9 71.1 76.5
[0082] The nanocomposite material NiSeZn(g-C3N4) / CNFs of the present invention is subjected to grafting modification, freeze denaturation treatment and secondary high temperature and high pressure calcination process, thereby enhancing the comprehensive properties of the composite material such as electrical conductivity (195S / cm), thermal conductivity (6.3×10 w / mk), bending strength (51.7 MPa) and compressive strength (91.4 MPa), which is beneficial to its application in hydrogen fuel cell composite bipolar plates. In addition, the raw materials used in the preparation method provided by the present invention are safe, and the cleaning liquid is recycled, thereby reducing the amount of waste liquid and avoiding environmental pollution.
Claims
1. A method for preparing a composite material NiSeZn(g-C3N4) / CNFs, characterized in that: It includes the following steps: S1, adding ethylene glycol to the carbon nanofibers after alkali treatment, adding silane coupling agent and melamine to carry out graft modification after ultrasonic treatment, washing the modified carbon nanofibers with water, and recovering the washing liquid; S2, adding the cleaning solution to dopamine and CE resin, stirring and reacting, drying, roasting, cooling, and then grinding the roasted product to nanometer scale; S3, preparing an aqueous solution containing melamine and ZnSO4 as a dispersion system A; S4, dispersing the modified carbon nanofibers obtained in step S1 in ethanol, adding nano-sized nickel selenide and the calcined product obtained in S2, and heating to obtain a dispersion system B; S5, adding dispersion system B to dispersion system A, and centrifuging after ultrasonic treatment; S6. Calcine the centrifuged sample to obtain the composite material NiSeZn(g-C3N4) / CNFs.
2. The preparation method according to claim 1, characterized in that: In step S1, the alkali treatment is performed by soaking in an alkaline solution; the soaking time is 1 to 2 hours, the amount of ethylene glycol used is 1:1 to 3 in a volume mass ratio of ethylene glycol to carbon nanofibers, and the unit is L:kg; the ultrasonic time is 20 to 30 minutes.
3. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of carbon nanofibers, silane coupling agent and melamine is 50-85: 1.7~3.6:0.8~1.5; the silane coupling agent is N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane coupling agent.
4. The preparation method according to claim 1, characterized in that: In step S1, the cleaned modified carbon nanofibers need to be subjected to freeze denaturation treatment, the freeze denaturation temperature is -10 to 0°C, and the treatment time is 3 to 10 hours.
5. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the cleaning solution to dopamine is 100-125:6.8-9.3, and the mass ratio of dopamine to CE resin is 1-2:3-7; The stirring reaction temperature is 50-65°C, and the reaction time is 24-40h; the calcination temperature is 200-320°C, and the calcination time is 50-70min; and the powder is ground to 200-600nm.
6. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of melamine to ZnSO4 is 15 to 21: 7.35~9, among which, The mass concentration of melamine is 13% to 20%.
7. The preparation method according to claim 1 is characterized in that in step S4, the amount of nickel selenide is added according to a mass ratio of nickel selenide to carbon nanofibers of 0.1 to 0.3:1; the heating temperature is 80°C and the heating time is 15 to 20 minutes.
8. The preparation method according to claim 1, characterized in that: In step S5, the addition rate of dispersed system B to dispersed system A is less than 1 L / min, and the ultrasonic treatment time is 1.5 to 2.3 h.
9. The preparation method according to claim 1, characterized in that: In step S6, the calcination is divided into two calcinations, the first calcination process is calcination at 600-750°C for 2.1-2.3h; the second high temperature and high pressure calcination process is calcination at 10-11Gpa and 1100-1200°C for 5-10min.
10. Use of the composite material NiSeZn(g-C3N4) / CNFs obtained by the preparation method according to any one of claims 1 to 9 in the preparation of hydrogen fuel cell composite bipolar plates.
Citation Information
Patent Citations
Metal bipolar plate and processing method
CN109560305A
Hydrogen fuel cell composite bipolar plate and preparation method thereof
CN117352765A
Modified conductive filler, composite bipolar plate containing modified conductive filler, and preparation method and application of modified conductive filler
CN117747169A
Fuel cell metal bipolar plate coating
CN210628419U
Amphiphilic g-C3N4 modified CNFs sponge with high thermal stability and preparation method of amphiphilic g-C3N4 modified CNFs sponge
CN110606991A